Cybereducation Jasa Pelayanan Pendidikan Pada Internet - Tung, Khoe Yao (Lembaga Penerbitan Universitas Esa Unggul, 2003)
AfterÃ‚Â Ã‚Â humanÃ‚Â teacher,Ã‚Â Ã‚Â theÃ‚Â Ã‚Â internetÃ‚Â Ã‚Â Ã‚Â wouldÃ‚Â Ã‚Â Ã‚Â representÃ‚Â Ã‚Â Ã‚Â Ã‚Â theÃ‚Â Ã‚Â mostÃ‚Â Ã‚Â importantÃ‚Â educational resources in the world if every student had a computer and internet networking. Teachers can use collage computer systems or home computers and individual internet account to educate themselves and then bring the benefit of the internet to their students by proxy. Not only the essence of lecture but all aspect education resources such as financial, tutor program, scholarships, college information. This paper identifies internet resources that can be particularly valuable teachers, students, and others with an interest in education.Kata Kunci : Cybereducation, Interconection Networking